RANCANG BANGUN SISTEM PEMANTAU RUANG PERALATAN NAVIGASI PADA AIRNAV INDONESIA CABANG MANADO BERBASIS INTERNET OF THINGS (IoT) - Kudampa, Gresstasya Narda; Pandey, Enjelika; Sawidin, Sukandar; Waroh, Anthoinete; Putung, Yoice (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The navigation equipment room is a critical facility that supports the safety and continuity of air navigation services; therefore, its environmental and electrical conditions must be maintained optimally. At the existing condition in AirNav Indonesia Manado Branch, monitoring activities are still carried out manually, which may lead to delays in detecting potential disturbances or equipment failures. This study aims to design and develop an Internet of Things (IoT)-based monitoring system capable of performing real-time and remote monitoring of the navigation equipment room. The research methodology includes hardware design using an ESP32 microcontroller integrated with temperature, smoke, and voltage sensors, as well as the development of a web-based application to display monitoring data. Sensor data are processed by the ESP32 and transmitted through an internet network, allowing technicians to access the information in real time from remote locations.The results show that the proposed system is capable of monitoring temperature in degrees Celsius, detecting smoke as an early indication of fire hazards, and accurately measuring electrical voltage stability. The system enables technicians to conduct monitoring activities without being physically present at the site, thereby improving response time to disturbances, minimizing the risk of equipment damage, and supporting the reliability and continuity of air navigation services.